Highly thixotropic, high temperature resistant and yellowing resistant photovoltaic solder strip UV glue, preparation method and glue application method
By using high thixotropic and high temperature and yellowing resistance in photovoltaic modules, the existing UV glue is not resistant to high temperature and yellowing resistance, and the stability and conductivity of welding are achieved, the connection needs of large-size and thick battery cells are met, and the cost and energy consumption of the components are reduced.
Patent Information
- Application Number
- CN202311221461.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-21
AI Technical Summary
In existing photovoltaic modules, UV glue is not resistant to high temperatures and yellowing, resulting in unstable welding and poor conductivity. It is difficult for traditional welding methods to meet the connection needs of large-size and thick battery cells.
UV glue with high thixotropic resistance to high temperature and yellowing resistance is adopted. The formula includes oligomers, active monomers, modified mixed powders, surface photoinitiators and deep photoinitiators. Through the modified mixed powder and an efficient photoinitiator system, the temperature and yellowing resistance of UV glue are improved.
It realizes the high temperature and yellowing resistance of UV glue, improves welding stability and conductivity, meets the connection needs of large-size and thick battery cells, and reduces the cost and energy consumption of components.
Smart Images

Figure CN117384580B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic materials, and in particular to a high-thixotropic, high-temperature-resistant and yellowing-resistant photovoltaic welding strip UV glue, a preparation method and a gluing method. Background Art
[0002] At present, the connection between cells in photovoltaic modules is mainly achieved by high-temperature welding of tin-coated copper strips. With the iteration of photovoltaic technology, the size and specifications of cells in photovoltaic modules will become larger and thinner in the future. Therefore, in order to prevent hidden cracks in cells, high-temperature welding technology is no longer applicable. In addition, as the size of the welding strip becomes thinner, the tensile force after welding no longer meets the requirements.
[0003] Patent CN114843360A proposes to use UV glue to fix copper wire to connect battery cells. This method replaces the traditional welding method, but it has many shortcomings. First, when copper wire is used to directly connect battery cells, there will be direct contact between copper wire and EVA, and the acetic acid molecules decomposed in EVA will corrode it. Secondly, only using UV glue to fix and omitting welding can easily cause poor contact between copper wire and battery cells and poor conductivity. In addition, the patent only proposes an implementation plan, and does not disclose the formula of its UV glue and the location of glue application. The existing UV glue formula on the market has severe yellowing at 200°C, which does not meet the use requirements of this technology.
[0004] Patent CN116135938 A proposes a method for applying UV glue to photovoltaic modules, which completely wraps the solder strips. A large amount of glue is used, and more EVA film is used during lamination to prevent the battery cells from breaking. This will inevitably increase the cost. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a highly thixotropic, high temperature and yellowing resistant photovoltaic welding strip UV adhesive, which solves the problem that the UV adhesive is not resistant to high temperatures and yellowing.
[0006] The technical solution adopted by the present invention to solve the technical problem is: a high thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV adhesive, comprising the following components by mass: oligomer: 40-60 parts, active monomer: 30-40 parts, modified mixed powder: 1-5 parts, surface photoinitiator: 1-5 parts, deep photoinitiator: 0.5-1 parts;
[0007] The modified mixed powder is a hydrophobic mixed powder, and the modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 100:2-5;
[0008] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4-6, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 1:1.5-3.
[0009] Furthermore, the oligomer is a difunctional polyurethane acrylate oligomer with a viscosity of 10000-15000 CPS.
[0010] Furthermore, the active monomer is TMPTA monomer or DHPA monomer.
[0011] Furthermore, the surface photoinitiator is photoinitiator 184, and the deep photoinitiator is photoinitiator 819.
[0012] Furthermore, the particle size of the mixed powder of silicon nitride and boron nitride is 50-100 nm.
[0013] The present invention also discloses a method for preparing a high thixotropic, high temperature resistant and yellowing resistant photovoltaic solder strip UV adhesive, comprising the mass proportion of the high thixotropic, high temperature resistant and yellowing resistant photovoltaic solder strip UV adhesive described above, and the steps of:
[0014] S100: Weigh a certain mass of mixed powder of gas silicon and boron nitride, obtain a modifier of 2-5% of the mass of the mixed powder, spray the modifier on the surface of the mixed powder, and mix it evenly.
[0015] S200: Weigh the active monomer and the mixed powder modified in step S100 according to the ratio, and mix the two together and stir them evenly.
[0016] S300: adding the oligomer to the mixture in step S200 and stirring evenly.
[0017] S400: Add the surface initiator and the deep photoinitiator to the mixture in step S300 in sequence, and stir evenly to obtain UV glue.
[0018] The present invention also discloses a method for applying UV adhesive for photovoltaic welding strips, comprising the UV adhesive prepared by the above-mentioned method for preparing the high thixotropic, high temperature and yellowing resistant photovoltaic welding strip UV adhesive, the steps of:
[0019] Step A: Select low-temperature tin-coated solder strips and arrange them on the silicon cell in sequence according to the corresponding gate line positions;
[0020] Step B: setting a rated pressure to closely fit the low-temperature tin-coated solder strip 1 to the silicon cell;
[0021] Step C: Maintain constant pressure and apply UV glue on both sides of the round solder strip by dispensing. The glue height does not exceed half of the solder strip diameter. The glue size is 2-3mm along the solder strip direction. The total glue length on both sides perpendicular to the solder strip does not exceed the solder strip diameter. The glue length on both sides is consistent. There are multiple glue points for a single solder strip of a single cell. The glue points are fine grid positions outside the main silver paste points, and the distance between each glue point is the same.
[0022] Step D: Use an arc-shaped UV lamp to radiate and cure the UV glue for 2-3 seconds;
[0023] Step E: When the cured battery cells are laminated, the lamination temperature is used to melt the tin layer, thereby achieving good conductive connection between the soldering tape and the battery cells.
[0024] The beneficial effects of the present invention are:
[0025] 1. This method uses UV glue to fix the solder strip, and matches it with a low-temperature tin-coated solder strip, so that the solder strip and the battery cell are doubly fixed, greatly improving the peeling force between the two. At the same time, it replaces the traditional infrared heating welding, and provides feasibility for thinning the battery cells at the component end and reducing costs and energy.
[0026] 2. The modified mixed powder is added to the UV glue formula system. The unique rheological properties of the mixed powder are used to prevent the glue from spreading before curing, thereby avoiding large-scale contamination of the battery cell.
[0027] 3. The mixed powder contains boron nitride with high heat transfer efficiency, which can quickly transfer heat to avoid the UV glue body temperature being too high, thereby improving the temperature resistance of the UV glue, thereby ensuring that the components can resist the high temperature problem caused by short circuit in a short time, so as to leave enough time for maintenance and processing without affecting continued use.
[0028] 4. This glue application scheme has a small application area, and the glue application area is on the backlight part of the solder strip, which utilizes the ineffective area of light and will not affect the reflection of light by the solder strip, thus not affecting the power of the component. Gluing on both sides will not cause the solder strip to be suspended, which is convenient for welding during the later lamination without generating deformation stress and causing cold solder joints. It also reduces the risk of battery cell breakage during lamination. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a structural schematic diagram of the gluing scheme of an embodiment of the present application.
[0030] Marked in the figure: low-temperature tin-coated solder strip 1, silicon battery cell 2, UV glue 3. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0032] The embodiment of the present application discloses a high thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV adhesive, which comprises the following components by weight: oligomer: 40-60 parts, active monomer: 30-40 parts, modified mixed powder: 1-5 parts, surface photoinitiator: 1-5 parts, deep photoinitiator: 0.5-1 parts;
[0033] The modified mixed powder is a hydrophobic mixed powder, and the modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 100:2-5;
[0034] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4-6, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 1:1.5-3.
[0035] Specifically, the oligomer selected in the above structure is a difunctional polyurethane acrylate oligomer, and its viscosity can reach 10000-15000 CPS.
[0036] Specifically, the active monomer in the above structure is TMPTA monomer or DHPA monomer.
[0037] Specifically, the surface photoinitiator in the above structure is photoinitiator 184 , and the deep photoinitiator is photoinitiator 819 .
[0038] Specifically, the oligomer and the active monomer can form a film-forming substance after the reaction. At the same time, the active monomer also plays the role of a diluent, which can adjust the viscosity of the glue and the hardness of the paint film. Two initiators are used in this scheme. The combined use of surface photoinitiator and deep photoinitiator can ensure the complete reaction of the paint film. The modified mixed powder has rheological properties, which can prevent the glue from spreading before curing.
[0039] In this UV glue, due to the addition of modified mixed powder and the unique rheological properties of the mixed powder, the glue will not spread before curing, thereby avoiding large-scale contamination of the battery cell. At the same time, since the mixed powder contains boron nitride with high heat transfer efficiency, it can quickly transfer heat to avoid the main body of the UV glue from being too high, thereby improving the temperature resistance of the UV glue, thereby ensuring that the component can resist the high temperature problem caused by short circuit in a short time, so as to leave sufficient time for maintenance and treatment without affecting continued use.
[0040] In this embodiment, the particle size of the mixed powder of gas silicon and boron nitride is 50-100 nm, specifically 50 nm, 80 nm, 100 nm, etc.
[0041] Specifically, the selection of the above-mentioned particle size range can ensure the transmittance of the photovoltaic welding ribbon UV glue after film formation. If the particle size is too large, the photovoltaic welding ribbon UV glue will become turbid after film formation.
[0042] The present invention also discloses a method for preparing a high thixotropic, high temperature resistant and yellowing resistant photovoltaic solder strip UV adhesive, comprising the mass proportion of the high thixotropic, high temperature resistant and yellowing resistant photovoltaic solder strip UV adhesive described above, and the steps are:
[0043] S100: Weigh a certain mass of mixed powder of gas silicon and boron nitride, spray a modifier on the surface of the mixed powder according to 2-5% of the mass of the mixed powder, and mix them evenly.
[0044] S200: Weigh the active monomer and the mixed powder modified in step S100 according to the ratio, and mix the two together and stir them evenly.
[0045] S300: adding the oligomer to the mixture in step S200 and stirring evenly.
[0046] S400: Add the surface initiator and the deep photoinitiator to the mixture in step S300 in sequence, and stir evenly to obtain UV glue.
[0047] The present invention also discloses a method for applying UV adhesive for photovoltaic welding strips, including the UV adhesive prepared by the above-mentioned method for preparing the high thixotropic, high temperature and yellowing resistant photovoltaic welding strip UV adhesive, characterized in that:
[0048] Step A: Select low-temperature tin-coated solder strips 1 and arrange them on the silicon cell 2 in sequence according to the corresponding gate line positions;
[0049] Step B: setting a rated pressure to closely fit the low-temperature tin-coated solder strip 1 to the silicon cell 2;
[0050] Step C: Maintain constant pressure and apply UV glue 3 on both sides of the round solder strip by glue dispensing. The glue height does not exceed half of the solder strip diameter. The glue size is 2-3mm along the solder strip direction. The total glue length on both sides in the direction perpendicular to the solder strip does not exceed the solder strip diameter. The glue length on both sides is consistent. There are multiple glue points for a single solder strip of a single cell. The glue points are fine grid positions outside the main silver paste points, and the distance between each glue point is the same.
[0051] Step D: Use an arc-shaped UV lamp to radiate and cure the UV glue for 2-3 seconds;
[0052] Step E: When the cured battery cells are laminated, the lamination temperature is used to melt the tin layer, thereby achieving good conductive connection between the soldering tape and the battery cells.
[0053] In the above method, when applying glue, the height of the glue does not exceed half of the diameter of the solder strip, and the total length of the glue applied on both sides of the solder strip in the perpendicular direction does not exceed the diameter of the solder strip, so that the glue application area can be in the backlight part of the solder strip, using the ineffective area of light, which will not affect the reflection of light by the solder strip, and thus will not affect the power of the component. In addition, the glue application on both sides will not cause the solder strip to be suspended, which is convenient for welding during the later lamination without generating deformation stress and causing cold solder joints, and also reduces the risk of battery cell breakage during lamination.
[0054] The following are specific embodiments of the present application:
[0055] Example 1
[0056] 1. Weigh the following components according to the following mass fractions: 40 parts of difunctional polyurethane acrylate oligomer, 40 parts of active monomer, 1 part of modified mixed powder, the particle size of the mixed powder is 50 nm, 2 parts of surface photoinitiator, and 0.5 parts of deep photoinitiator;
[0057] The modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 50:1;
[0058] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 2:3.
[0059] 2. According to the preparation method of high thixotropic, high temperature resistant and yellowing resistant photovoltaic welding tape UV adhesive, the above weighed components are mixed together to form a uniform UV adhesive 3 with a viscosity of 18000 CPS.
[0060] 3. Select low-temperature tin-coated solder strips 1 of corresponding specifications and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0061] Example 2
[0062] 1. Weigh the components according to the following mass proportions: 40 parts of difunctional polyurethane acrylate oligomer, 40 parts of active monomer, 2 parts of modified mixed powder, the particle size of the mixed powder is 50 nm, 2 parts of surface photoinitiator, and 0.5 parts of deep photoinitiator.
[0063] The modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 50:1;
[0064] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 2:3.
[0065] 2. According to the preparation method of high thixotropic, high temperature resistant and yellowing resistant photovoltaic welding tape UV adhesive, the above weighed components are mixed together to form a uniform UV adhesive 3 with a viscosity of 21000 CPS.
[0066] 3. Select low-temperature tin-coated solder strips 1 of corresponding specifications and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0067] Example 3
[0068] 1. Weigh the following components according to the following mass fractions: 40 parts of difunctional polyurethane acrylate oligomer, 40 parts of active monomer, 3 parts of modified mixed powder, the particle size of the mixed powder is 50 nm, 2 parts of surface photoinitiator, and 0.5 parts of deep photoinitiator;
[0069] The modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 50:1;
[0070] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 2:3.
[0071] 2. According to the preparation method of high thixotropic, high temperature resistant and yellowing resistant photovoltaic welding tape UV adhesive, the above weighed components are mixed together to form a uniform UV adhesive 3 with a viscosity of 23000 CPS.
[0072] 3. Select low-temperature tin-coated solder strips 1 of corresponding specifications and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0073] Example 4
[0074] 1. Weigh the components according to the following mass proportions: 40 parts of difunctional polyurethane acrylate oligomer, 40 parts of active monomer, 3 parts of modified mixed powder, the particle size of the mixed powder is 100 nm, 2 parts of surface photoinitiator, and 0.5 parts of deep photoinitiator.
[0075] The modified mixed powder is a mixture of mixed powder and a mixture, and the ratio of the mixed powder to the mixture is 50:1;
[0076] The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is: gas silicon: boron nitride = 1:4, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mixed mass ratio of silane coupling agent and oily anti-settling agent is: silane coupling agent: oily anti-settling agent = 2:3.
[0077] 2. According to the preparation method of high thixotropic, high temperature resistant and yellowing resistant photovoltaic welding tape UV adhesive, the above weighed components are mixed together to form a uniform UV adhesive 3 with a viscosity of 25000 CPS.
[0078] 3. Select low-temperature tin-coated solder strips 1 of corresponding specifications and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0079] Comparative Example 1
[0080] 1. Weigh the components according to the following mass parts: 40 parts of difunctional polyurethane acrylate oligomer, 40 parts of active monomer, 2 parts of surface photoinitiator, and 0.5 parts of deep photoinitiator.
[0081] 2. According to the preparation method of UV glue 3, mix the weighed components together to form a uniform UV glue 3 with a viscosity of 8000 CPS.
[0082] 2. Select low-temperature tin-coated solder strips 1 of corresponding specifications and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0083] Comparative Example 2
[0084] 1. Weigh the components according to the following mass proportions: 2-functional polyurethane acrylate oligomer: 40 parts, active monomer: 40 parts, mixed powder (unmodified): 3 parts, the particle size of the mixed powder is 100 nm, surface photoinitiator: 2 parts, deep photoinitiator: 0.5 parts.
[0085] 2. According to the preparation method of UV glue 3, mix the weighed components together to form a uniform UV glue 3 with a viscosity of 6000 CPS.
[0086] 3. Select low-temperature tin-coated solder strips 1 of corresponding specifications, and arrange them in sequence according to the corresponding grid line positions; set the rated pressure to tightly fit the low-temperature tin-coated solder strips 1 and the silicon cell 2; maintain constant pressure, and apply glue on both sides of the circular solder strip by dispensing, the glue height shall not exceed half of the diameter of the solder strip, the glue size shall be 3mm along the direction of the solder strip, the total glue length on both sides perpendicular to the solder strip shall not exceed the diameter of the solder strip, and the glue length on both sides shall be consistent. The number of glue points for a single solder strip of a single cell is 4, and the glue points are the fine grid positions outside the main silver paste points, and the interval distance at each time point is the same; use an arc-shaped UV lamp to radiate and cure the UV glue 3, and the curing time is 3S; when the cured cell is laminated according to the normal process, the lamination temperature is used to melt the tin layer to achieve good conductive connection between the solder strip and the cell.
[0087] The following is a test of light transmittance, peeling force between solder ribbon and silicon wafer, and yellowing resistance level of the above four embodiments and two comparative examples.
[0088] Among them, the above tests were conducted using a transmittance tester, a cell tensile tester and a QUV test standard.
[0089]
[0090] It can be found from Examples 1-3 that as the amount of mixed powder is gradually added, the viscosity thereof shows an overall increasing trend. The increase of mixed powder will be more conducive to shaping after gluing, ensuring that UV glue 3 does not flow flat before light exposure. At the same time, the addition of mixed powder will affect the light transmittance of the cured glue layer. Within an appropriate range, the light transmittance will be greater than 85%, which will not affect normal use.
[0091] By comparing Examples 3 and 4, it can be found that as the particle size of the mixed powder increases, the light transmittance is greatly reduced and the temperature resistance is significantly improved.
[0092] It is found from Example 1 and Comparative Example 1, or Example 2 and Comparative Example 1, or Example 3 and Comparative Example 1 that without adding mixed powder, the viscosity is significantly reduced and construction is not easy.
[0093] It is found from Example 1 and Comparative Example 2, or Example 2 and Comparative Example 2, or Example 3 and Comparative Example 2 that the addition of unmodified mixed powders has poor dispersibility, which easily causes the mixed powders to agglomerate, resulting in poor light transmittance.
[0094] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV adhesive, characterized in that: The following components are included in proportion by mass: Oligomer: 40-60 parts, active monomer: 30-40 parts, modified mixed powder: 1-5 parts, surface photoinitiator: 1-5 parts, deep photoinitiator: 0.5-1 parts; The modified mixed powder is a hydrophobic mixed powder, which is a mixture of a mixed powder and a modifier, and the ratio of the mixed powder to the modifier is 100:2-5; The mixed powder is gas silicon and boron nitride, the mass ratio of gas silicon to boron nitride is gas silicon: boron nitride = 1:4-6, the modifier is a mixture of silane coupling agent and oily anti-settling agent, the mass ratio of silane coupling agent to oily anti-settling agent is silane coupling agent: oily anti-settling agent = 1:1.5-3; Its preparation method is: S100: weigh a certain mass of mixed powder of gas silicon and boron nitride, obtain a modifier of 2-5% of the mass of the mixed powder, spray the modifier on the surface of the mixed powder, and mix it evenly; S200: weighing the active monomer and the mixed powder modified in step S100 according to the ratio, and mixing the two together and stirring them evenly; S300: adding the oligomer to the mixture in step S200 and stirring evenly; S400: adding a surface initiator and a deep photoinitiator to the mixture of step S300 in sequence, and stirring evenly to obtain a UV adhesive; The sizing method is: Step A: Select low-temperature tin-coated solder strips (1) and arrange them in sequence on the silicon solar cell (2) according to the corresponding gate line positions; Step B: setting a rated pressure to tightly fit the low-temperature tin-coated solder strip (1) and the silicon cell (2); Step C: maintaining constant pressure, applying UV glue (3) on both sides of the round solder strip by glue dot method, the glue application height does not exceed half of the solder strip diameter, the glue application size is 2-3 mm along the solder strip direction, the total glue application length on both sides in the direction perpendicular to the solder strip does not exceed the solder strip diameter, and the glue application length on both sides is consistent, the number of glue application points for a single solder strip of a single cell is multiple, the glue application points are fine grid positions outside the main silver paste points, and the distance between each glue application point is the same; Step D: Use an arc-shaped UV lamp to radiate and cure the UV glue for 2-3 seconds; Step E: When the cured battery cell is laminated, the lamination temperature is used to melt the tin layer, so as to achieve good conductive connection between the soldering ribbon and the battery cell; The oligomer is a difunctional polyurethane acrylate oligomer; The active monomer is TMPTA monomer or DHPA monomer.
2. The high thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV adhesive according to claim 1, characterized in that: The surface photoinitiator is photoinitiator 184, and the deep photoinitiator is photoinitiator 819.
3. The high thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV adhesive according to claim 1, characterized in that: The particle size of the mixed powder of gas silicon and boron nitride is 50-100 nm.
Citation Information
Patent Citations
UV structure fixing adhesive composition for photovoltaic module assembly and photovoltaic module
CN116135938A
Preparation method of UV moisture dual-cured heat-conducting adhesive
CN112300746A
Photovoltaic module welding mode
CN116673645A